Racism and hate speech – A critique of Scanlon's Contractual Theory. Issue 1 (3rd July 2019) - Cohen-Almagor, Raphael
ABSTRACT: The First Amendment is an important value in American liberal polity. Under this value, racism, hate speech and offensive speech are protected speech. This article scrutinizes one of the clear representatives of the American liberal polity – Thomas Scanlon. The paper tracks the developments in his theory over the years. It is argued that Scanlon's arguments downplay tangible harm that speech might inflict on its target victim audience. Scanlon's distinction between participant interests, audience interests, and the interests of bystanders is put under close scrutiny. The article criticizes viewpoint neutrality and suggests a balancing approach, further arguing that democracy is required to develop protective mechanisms against harm-facilitating speech as well as profound offences. Both should be taken most seriously.